THE EXPRESSION OF «NEW REALISM» IN THE WORKS OF ZAKHAR PRILEPIN (USING THE EXAMPLE OF THE NOVEL SANKYA) (Web of Teachers: Inderscience Research, 2025)
The article examines the trend of «new realism» through the prism of the work of Russian writer and publicist Zakhar Prilepin. An attempt has been made to analyze the author's novel «Sankya». The relevance of the topic is due to the modern approach to the description of pressing problems and acute social issues. «New Realism» is the literature of the young, which is perhaps becoming a new form of classical Russian literature.